Palha de milho: restos culturais como potencial poético - Abadie, Vanderleia Rodrigues (2017)
This Master's research began with the use of corn-straw on canvas-paintings and collages that afterwards would become objects. The present research deals with how it became possible to use straw to compose concepts that cover environmental art, the plastic creation of objects composed of straw, Ecology and Agriculture. Besides the procedural and poetic character of the writing, the compositive experience with straw was investigated, where it was proposed a resumption of the latencies experienced during childhood in a city in the interior of Rio Grande do Sul, experiences that supported the research. These experiences led to thinking about the forms of this element in constant transformation - CORN STRAW, straw shape, shapes in space, valuing the corporality found, exposing it in a context that encompasses Ecology and Art. As a reference to Environmental Art, we present contemporary artists such as Jorge Mena Barreto and Franz Kracjberger, contemporary artists related to the movement known as Environmental Art. In this way, the development of maize straw was developed as a poetic potential linked to social responsibility.